"Leading Better Care": An evaluation of an accelerated coaching intervention for clinical nursing leadership development. (30th March 2018) - Cable, Stuart; Graham, Edith
Abstract : Aim: Outcomes of an accelerated co‐active coaching intervention for senior clinical nursing leadership development. Background: Co‐active coaching is characterized by a whole person approach, commitment to deep learning and conscious action through supportive compassionate and courageous coach–coachee partnership. The national leadership capabilities framework, "Step into Leadership", was used for development and evaluation. Methods: 116 senior clinical nurse leaders attended one face‐to‐face induction day and received a total of 3 hours of one‐to‐one telephone coaching and two virtual peer group facilitated sessions. Evaluation used primarily qualitative descriptive methods with iterative review of emerging themes. Results: Capability mapping indicated self‐leadership development as the most frequently cited need. Improvements in self‐confidence, capacity for reflection and bringing whole self into the work were reported to deliver enhancement in team and service performance. Conclusions: Co‐active coaching supported deep analysis by individuals. Focus on self, rather than behaviours provoked reflection on perspectives, mindsets, beliefs and approaches which can lead to more sustainable behaviour and support service change. Implications for Nursing Management: Investment in a co‐active coaching approach offers bespoke support for clinical leaders to develop self‐leadership capability, a precursor to delivering positive impacts on care.